Rapid Speed Modulation of a Rotary Total Artificial Heart Impeller. Issue 9 (19th September 2016) - Kleinheyer, Matthias; Timms, Daniel L.; Tansley, Geoffrey D.; Nestler, Frank; Greatrex, Nicholas A.; Frazier, O. Howard; Cohn, William E.
Abstract: Unlike the earlier reciprocating volume displacement–type pumps, rotary blood pumps (RBPs) typically operate at a constant rotational speed and produce continuous outflow. When RBP technology is used in constructing a total artificial heart (TAH), the pressure waveform that the TAH produces is flat, without the rise and fall associated with a normal arterial pulse. Several studies have suggested that pulseless circulation may impair microcirculatory perfusion and the autoregulatory response and may contribute to adverse events such as gastrointestinal bleeding, arteriovenous malformations, and pump thrombosis. It may therefore be beneficial to attempt to reproduce pulsatile output, similar to that generated by the native heart, by rapidly modulating the speed of an RBP impeller. The choice of an appropriate speed profile and control strategy to generate physiologic waveforms while minimizing power consumption and blood trauma becomes a challenge. In this study, pump operation modes with six different speed profiles using the BiVACOR TAH were evaluated in vitro. These modes were compared with respect to: hemodynamic pulsatility, which was quantified as surplus hemodynamic energy (SHE); maximum rate of change of pressure (dP/dt); pulse power index; and motor power consumption as a function of pulse pressure. The results showed that the evaluated variables underwent different trends in response to changes in the speed profile shape. The findings indicated a possible trade‐off between SHE levels and flow rate pulsatility related to the relative systolic duration in the speed profile. Furthermore, none of the evaluated measures was sufficient to fully characterize hemodynamic pulsatility.